Analysis of Experimental Results Measurement of Electric Impedance Value on Liquid with Injection Flow on Parallel Plate - Gianita Anastasia Salamena; Abdurrouf Abdurrouf; Didik Rahadi Santoso (Natural B, Journal of Health and Environmental Sciences, 2017)
This paper discusses the results of experimental measurement of the electrical impedance of liquids in parallel and perpendicular position to the direction of current injection. Experiments carried out on three different types of liquid i.e. distilled water, mineral water, and milk. Each liquid is placed in a container box with volume of 2,5cm x 2,5cm x 2,5cm. The electrode is located in the middle of the upright side of the container, forming two pairs of parallel plates, where one pair of parallel plate will serve as the current electrode. Current signal frequency range used in this experiment is 1Hz-500Hz. Experimental results obtained some things such as each liquid has a different electrical characteristic, distilled water has much larger electrical impedance compared to the mineral water and milk. Area of the electrode affects the measured impedance values on each liquid; the larger area of the electrode will decrease impedance value. The position of the electrode against the direction of flow injection showed the difference in impedance values measured, where the impedance measured at liquid injection electrode direct current is greater than the value of the impedance measured at liquid electrodes perpendicular injection current.